Ética, bioética y calidad educativa como dimensiones de la formación integral de los estudiantes de Odontología - Castro Rodríguez, Antonia (2022)
Currently, a series of transformations are taking place for professional practice in the field of oral health and, along with these changes, concerns and debates arise about the relevance and updating of university training. This article aims to connect the deliberation on the meaning of “ethical training”, “bioethical training”, “bioethical health”, “educational quality” and “quality higher education”, as dimensions that are questioned on the comprehensive training of the dental career student, in a context of transformation produced by technological and social innovations in the field of professional practice; this through the review of studies conducted in the period 2014-2022. For which, a set of articles was compiled by searching Scopus and applied qualitative documentary analysis based on the results provided by each study. The search terms ethical training, bioethical training and educational quality were used, through critical sampling 32 articles were selected for the study. The analysis concludes that for the integration of ethics, bioethics and educational quality, they should be assumed as conscious practices of daily life, with social relevance and oriented through models that reflect the complex reality.